Deep sequencing analysis of microRNAs in bovine sperm. Issue 11 (3rd October 2014) - Du, Yue; Wang, Xiangguo; Wang, Bo; Chen, Wuju; He, Rongjun; Zhang, Lei; Xing, Xupeng; Su, Jianmin; Wang, Yongsheng; Zhang, Yong
SUMMARY microRNAs (miRNAs) are small non‐coding RNAs that participates in the regulation of many physiological pathways, but a role for spermatozoon‐delivered miRNAs in fertilization and embryonic development remains controversial. A library of miRNAs in bovine sperm was constructed using Illumina high‐throughput sequencing technology, along with the predication and the pathway analysis of target genes. miRNAs in mammalian spermatozoon were systematically investigated, and a protocol for RNA isolation from the cauda region of an epididymal biopsy was established. Unique sequences that were 18–26 nucleotides in length were mapped to specific precursors in miRBase 20.0 using BLAST. A total of 951 known miRNAs and 8 novel, highly expressed miRNA candidates were identified. The search for endogenous sperm miRNAs will contribute to a preliminary database for functional and molecular mechanistic studies in embryonic development and sperm epigenetic programming. Mol. Reprod. Dev. 81: 1042–1052, 2014. © 2014 Wiley Periodicals, Inc.